Branding J & K Herbaceous Wealth - Andotra, Neetu (Indian Journal of Marketing, 2005)
A marketer is continually reminded of the need for product differentiation by building strong brand identities and decries imitation Brand building and its monitoring builds loyal customers willing to pay more for a brand that no alternative can provide. It confers certain marketing advantage such as reduced marketing costs, more new customers, greater trade leverage and other loyalty related marketing advantages, such as favorable word of mouth and greater resistance among loyal consumers to competitive strategies. Branding besides serving associative cues for information retrieval, serve as predictive cues about product performance. Consumers satisfied with a certain brand are unlikely to discontinue the brand choice unless the price differential covers the thinking costs as defined by Shugan. Similarly, Assael (1987) describes that prior satisfaction with a brand leads to repeat purchase which in turn accelerate habitual buying. Research studies have shown that ownership of brands of more inundane products provides valued bridges to family, friends, or neighbors.